BULLS COMPARATION THROUGH FROZEN SEMEN PRODUCED AT TECHNICAL SERVICES ARTIFICIAL INSEMINATION UNIT BATURITI REGION - ., Ashari; Ardika, I N.; Sarini, N. P. (Jurnal Peternakan Tropika, 2018)
This study aims to compare males through the quality of frozen semen produced in the Technical Service Unit of Artificial Insemination Center of Baturiti Region. This study used frozen semen from 10 bulls those frozen semen then were evaluated then sperm motility, concentration and percentage of sperm live were observed. The design used in this study was Completely Randomized Design (RAL) and each treatment was repeated three times. The study showe that there was no signiticant difference (P>0.05) to all parameters observed of bulls rised at the center. Sperm concentration of all bulls ranged between 41.25x10 6 to 59.38x10 6 spermatozoa/ml. While sperm motility between 41.67% to 46.67% and the percentage live sperm, ranged between 21,05 to 32,50 %. It can be concluded that all the frozen semen produced from the bulls rised at the Technical Services Unit of the Baturiti Insemination Center is in good condition and can be used for insemination. Keywords:   frozen semen, concentration, motility and percentage of spermatozoa